Heavy Metal Concentrations in Avicennia alba from the Western Coast of Dumai City, Riau Province - Yona, Fitria Mai; Amin, Bintal; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2025)
Coastal ecosystems play a crucial role in supporting biodiversity, but are increasingly threatened by heavy metal pollution from industrial and domestic activities. The mangrove species Avicennia alba can absorb heavy metals through phytoremediation processes, making it a promising bioindicator of environmental contamination. This study aimed to analyze the concentrations and variations in the accumulation of lead (Pb) and copper (Cu) in A. alba roots, stems, and leaves along the western coast of Dumai City, Riau Province. Fieldwork was conducted from January to February 2025 at two sampling sites: Pangkalan Sesai Village (Station 1) and Purnama Village (Station 2). Heavy metal concentrations were determined using Atomic Absorption Spectrophotometry (AAS) following wet digestion. Environmental parameters were also measured, including temperature, salinity, and pH. Data analysis involved descriptive statistics, non-parametric tests, and independent t-tests. The results indicated that Pb and Cu were present in all plant parts. The highest concentration of Pb was found in the stems (7.05 µg/g), while Cu was most concentrated in the roots (5.38 µg/g). No statistically significant differences were observed among plant parts (p > 0.05); however, a significant spatial difference in Pb concentrations between the two stations was detected (p < 0.05). These findings suggest that anthropogenic activities and local water quality conditions likely Influence the observed variations. Overall, A. alba demonstrates strong potential as a bioindicator species for monitoring heavy metal contamination in coastal environments.